Neuralized is expressed in the alpha/beta lobes of adult Drosophila mushroom bodies and facilitates olfactory long-term memory formation. - Pavlopoulos, E.; Anezaki, M.; Skoulakis, E.M.C. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Memory formation involves multiple molecular mechanisms, the nature and components of which are essential to understand these processes. Drosophila is a powerful model to identify genes important for the formation and storage of consolidated memories because the molecular mechanisms and dependence of these processes on particular brain regions appear to be generally conserved. We present evidence that the highly conserved ubiquitin ligase Neuralized (Neur) is expressed in the adult Drosophila mushroom body (MB) alpha/beta lobe peripheral neurons and is a limiting factor for the formation of long-term memory (LTM). We show that loss of one copy of neur gene results in significant LTM impairment, whereas overexpression of Neur in the peripheral neurons of the alpha/beta lobes of the adult MBs results in a dosage-dependent enhancement of LTM. In contrast, learning, early memories, or anesthesia-resistant memory are not affected. We also demonstrate that the role of Neuralized in LTM formation is restricted within the neurons of the periphery of the alpha/beta lobes, and we suggest that this structural subdivision of the MBs participates in the formation of LTM.